(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2025)
Background: The role of hotel facilities in tourists’ selection of star-category hotels is an essential area of focus, as it aims to understand guests’ preferences and improve service offerings. This research study explores the influence of hotel facilities on tourist decision-making with regard to visiting heritage arc cities, such as Agra, Lucknow and Varanasi in Uttar Pradesh. Objective: The primary objectives of this research was to examine the influence of hotel facilities on tourists’ selection of star-category hotels in the state of Uttar Pradesh and to recommend strategies for hotel professionals to upgrade amenities and services that align with customer preferences. Methodology: A descriptive research design was followed to conduct this research. Data was obtained in December 2024 through a questionnaire based survey conducted from 273 tourists who had experienced the star category hotels in Agra, Lucknow and Varanasi. Data was analyzed through weighted means and standard deviations. Results: The findings suggest that room service/ in-room dining (Weighted Mean = 4.12), restaurants/coffee shops (Weighted Mean = 3.91) and business facilities like business centers (Weighted Mean = 3.85) and Wi-Fi (Weighted Mean = 3.67) are primary determinants of hotel choice. They emphasize convenience, comfort and connectivity as important. By comparison, places such as shopping arcades (Weighted Mean = 2.93), fitness centers (Weighted Mean = 2.76) and babysitters (Weighted Mean = 2.59) exert a less significant influence on tourists’ choice. Hotels need to concentrate on priority services while upgrading secondary amenities to accommodate varied guest expectations. Conclusion: This study highlights the importance of core facilities such as room service, food and business services in bringing in tourists to star-category hotels. The hoteliers must make developing these services a top priority while enhancing less significant ones such as fitness clubs and babysitting to attract more customers. The synchronization of services with customer requirements enhances satisfaction and loyalty.